Evaluation of a commercial IgE ELISA in comparison with IgA and IgM ELISAs, IgG avidity assay and complement fixation for the diagnosis of acute toxoplasmosis - Kodym, P; Machala, L; Rohácová, H; Sirocká, B; Malý, M (Clinical microbiology and infection, 2007)
A panel of sera from patients with known case histories representative of acute toxoplasmosis (primarily lymphadenopathy, n = 106), latent toxoplasmosis (asymptomatic, n = 368) and negative samples (n = 54) was used to evaluate the capacity of five serological tests to differentiate among patients with acute or latent toxoplasmosis and non-infected individuals. Positive IgA, IgE and IgM ELISA results and low IgG avidity and complement fixation test (CFT) titres of >or=256 were considered to be indicative of acute toxoplasmosis. The most sensitive methods were IgM ELISA (98.1%) and CFT (97.1%), albeit with low specificity (65.0% and 64.5%, respectively) and positive predictive values (43.3% and 42.7%, respectively). IgG avidity assay and IgE ELISA had the highest specificity (97.7% and 91.7%, respectively) and the highest positive predictive values (89.4% and 75.6%, respectively). The best association between serological results and clinical findings was obtained with IgE ELISA (86%, as expressed via Youden's index). In a subset of 259 samples categorised by the period between the onset of clinical symptoms and sampling, >50% of patients had enlarged lymph nodes for <4 months, despite a broad range of differences. However, IgM remained positive for 12-18 months, IgA for 6-9 months and IgE for 4-6 months. IgG avidity remained low for a maximum of 4 months, after which avidity increased despite the persistence of enlarged lymph nodes and a positive IgE assay. Detection of IgE appears to be a highly specific test for confirming the acute nature of Toxoplasma infections that have been detected by other sensitive methods.
Keywords: senioři; toxoplazmóza; Antibody Affinity; Immunoglobulin E; senioři nad 80 let; imunoglobulin G; afinita protilátek; kojenec; Antibodies, Protozoan; mladiství; Middle Aged; Sensitivity and Specificity; mužské pohlaví; Immunoglobulin M; Infant; Adult; dítě; Child; Immunoglobulin A; Toxoplasmosis; imunoglobulin M; Aged, 80 and over; Child, Preschool; Immunoglobulin G; sérologické testy; Infant, Newborn; ženské pohlaví; ELISA; novorozenec; zvířata; Humans; předškolní dítě; imunoglobulin E; Serologic Tests; komplement fixační testy; Toxoplasma; Acute Disease; protilátky protozoální; lidé středního věku; imunoglobulin A; Complement Fixation Tests; senzitivita a specificita; akutní nemoc; dospělí; Enzyme-Linked Immunosorbent Assay; Female; Aged; Adolescent; lidé; Male; Animals